2022
DOI: 10.3390/jof8060589
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Metabolic Activity of Fungi Causing Biodeterioration of Canvas Paintings

Abstract: Research into the biodeteriorative potential of fungi can serve as an indicator of the condition of heritage items. Biodeterioration of canvas paintings as a result of fungal metabolic activity is understudied with respect to both the species diversity and mechanisms involved. This study brings new evidence for the physiology of fungi biodeteriorative capacity of canvas paintings. Twenty-one fungal isolates were recovered from four oil paintings (The Art Museum, Cluj-Napoca) and one gouache painting (private c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…These substrates contained components typically encountered in historic canvas paintings. The study revealed that the genus Aureobasidium exhibited the highest level of biodeterioration potential, with Cladosporium, Penicillium, Trichoderma, and Aspergillus following in decreasing order of potential impact [50]. The formation of acid metabolites and solubilization of calcite in the case of fungal isolates indicated probable degradation.…”
Section: Discussionmentioning
confidence: 96%
“…These substrates contained components typically encountered in historic canvas paintings. The study revealed that the genus Aureobasidium exhibited the highest level of biodeterioration potential, with Cladosporium, Penicillium, Trichoderma, and Aspergillus following in decreasing order of potential impact [50]. The formation of acid metabolites and solubilization of calcite in the case of fungal isolates indicated probable degradation.…”
Section: Discussionmentioning
confidence: 96%
“…Ascomycota is one of the most diverse and ubiquitous phylum of eukaryotes, present in numerous ecological habitats [15]. More than 40% of all Ascomycota are lichenized and, according to the literature, as a result of their fungal metabolic activity and ability to hydrolyze short-chain fatty acids, in addition to amylolytic, and occasionally proteolytic and glycolytic activities, most of the fungal species that are involved in the deterioration of cultural heritage belong to this phylum [16,17]. Chlorophyta is a taxon of eukaryotic green algae that often assembles symbiotic relationships with fungi to form lichens.…”
Section: Eukaryote Communitiesmentioning
confidence: 99%
“…Also, conservation-restoration interventions use preferably organic materials [2]. Nevertheless, there is little information on microbial biodeterioration of these materials [2,3,7,[9][10][11]. Only a few studies so far have focused on the microbial enzymes responsible for degradation of canvas paintings [11][12][13], and they were based on rapid, low-cost plate assays [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is little information on microbial biodeterioration of these materials [2,3,7,[9][10][11]. Only a few studies so far have focused on the microbial enzymes responsible for degradation of canvas paintings [11][12][13], and they were based on rapid, low-cost plate assays [14,15]. The fungal genera recognized for their broad range of enzymatic activities were Aspergillus, Cladosporium, and Penicillium [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation